Bilinear control processes : with applications to engineering, ecology, and medicine - Mohler, Ronald R.; ScienceDirect eBooks (New York : Academic Press, 1973)
Bilinear control processes: with applications to engineering, ecology, and medicine.
Includes bibliographical references and indexes.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Elsevier
Keywords: Control theory; Automatic control; Biological control systems; Mathematics; TECHNOLOGY & ENGINEERING -- Automation; TECHNOLOGY & ENGINEERING -- Robotics; Automatic control; Biological control systems; Control theory; Bilinear control systems; Electronic books